Worker productivity during Covid-19 and adaptation to working from home - Ashley Burdett; Ben Etheridge; Li Tang; Yikai Wang (University of Essex, Institute for Social and Economic Research (ISER), 2023)
We examine reported productivity changes of workers over the course of the Covid-19 pandemic, which we validate against external metrics. On average, workers report being at least as productive as before the pandemic's onset. However, this average masks substantial heterogeneity, which is linked to job quality, gender, the presence of children, and ease of working from home. As the pandemic progressed, those who previously performed well at home were more likely to remain there. Building on these findings, we estimate factors affecting productivity outcomes across locations controlling for endogenous selection. We find that those in "good" jobs (with managerial duties and working for large firms) were advantaged specifically in the home environment. More generally we find an effect of key personality traits - agreeableness and conscientiousness - on productivity outcomes across locations.
Keywords: D24; I24; I30; J21; J22; J24; L23; 330; Worker Productivity; Working From Home; COVID-19; Inequality; Gender